Analysis on three-core power cable temperature field and ampacity model under typical laying environment - Hu, Zhenxing; Ye, Xueyong; Li, Qian; Luo, Xiaokang; Zhao, Yizheng; Zhang, Hao; Zhang, Liang (Frontiers in Energy Research, 2024)
The current carrying capacity of power cables is an important parameter for the operation and scheduling of power cables, which is limited by the maximum allowable operating temperature of the cables. Establishing a cable temperature field and current carrying capacity model considering the influence of airflow in complex environments is of great significance for studying cable current carrying capacity. Based on the coupling theory of electric field and heat flow field, a temperature field and current carrying capacity analysis model for high-voltage three core cross-linked polyethylene cable and its laying environment was established using finite element analysis technology. Studied the effects of external air velocity and temperature on the current carrying capacity of cables under two laying methods: direct burial and air laying. Research has shown that the allowable operating time of short-term emergency current carrying capacity of cables is positively correlated with their size, and inversely proportional to the initial temperature of the cable core. The steady-state and transient analysis results of this model provide important reference value for cable operation scheduling, and the correctness and effectiveness of the model have been further verified through experiments based on actual scenarios.